(untitled) (Contemporary Mathematics, 2023)
The dynamics of the host viral load during triple coinfection between severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), influenza A, and the syncytial virus is studied. To explore how the host cells, the infected cells, and the viral load behave as a function of time, numerical simulations are performed. Via numerical simulations, the differential equations are analyzed by considering initial conditions. Since the numerical simulations are performed by using the physiological parameters, the model system can genuinely help to understand the viral dynamics either in vivo or in vitro. The result obtained in this work depicts that a higher viral load is exhibited when the three viruses simultaneously infect the host cells than in a single infection case. This indicates that simultaneous infection with SARS-CoV-2, influenza A, and syncytial viruses might be associated with a higher morbidity and mortality rate as these viruses by cooperating with each other facilitate a higher infection rate. Using physiological parameters, we further study the correlation between viral load, susceptible cells, and infected cells. As the three viral species cooperatively infect the host cells, the number of infected cells rises resulting in a higher viral load. Since influenza A has a higher viral reproduction rate than the two types of virus, it dictates the overall dynamics as it has a competitive advantage. Since these viruses share the same resources, the virus production of a given virus can be affected by the other. The interference of these viruses relies on the initial dose, the order of infection, and the strain of the virus. We show that when influenza A and syncytial viruses are initiated a few days after SARS-CoV-2 establishes an infection, while SARS-CoV-2 thrives, and the other two viruses fail to establish an infection. The viruses with an initially higher dose have also a survival advantage. Furthermore, the effect of lymphocytes on the overall viral dynamics is explored via numerical simulations. Since SARS-CoV-2 targets several types of cells and organs, a higher SARS-CoV-2 viral load can be also associated with a higher morbidity and mortality rate.